Representaciones de la nación en el ensayo argentino. Una lectura crítica a la centralidad pampeana. Representations of the nation in the argentine essay. A critical reading to the pampean centrality - Elbirt, Ana Laura (Latinoamérica. Revista de Estudios Latinoamericanos, 2017)
En este artículo se examina el rol estratégico del ensayo argentino en la construcción de una identidad nacional, abarcando tres períodos: la Generación de 1837, la Generación de 1880 y el movimiento del Centenario de la República. Asimismo, se recupera la perspectiva de un intelectual “extracéntrico”, Bernardo Canal Feijóo, quien critica el ensayo de supuesta temática nacional, afirmando que la literatura argentina es la expresión de una sola porción del país: el litoral o la pampa. Se analiza su ensayo de “regionalización” de las producciones culturales, privilegiando un área compleja y dinámica: el “noroeste” argentino. Abstract: This article analyses the strategic role of the Argentinian essay in the building up of a national identity. The study encompasses three moments: the generation of 1837, the generation of 1880, and the Centenary of the Republic movement. It retrieves also the perspective of an “extra-centric” intellectual, Bernando Canal Feijóo, who criticizes the socalled national-themed essay, claiming that Argentinian literature is the expression of a single portion of the country: the coast, or the pampas. The author looks into Feijoo’s essay on the “regionalization” of cultural works, where he favours a complex and dynamic area, the Argentinian “northwest”. Key words: Essay, Nation, Argentina,